Serum paraoxonase-1 activity in Egyptian premenopausal women with metabolic syndrome and its relation with recurrent pre-eclampsia risk - Moushira Zaki, Walaa A Basha, Walaa Yousef, Ahmed S Ismail, Eman Youness, Tamer Hussein, Osama Azmy (Journal of Applied Pharmaceutical Science, 2018)
Background: Association of paraoxonase-1 (PON-1) with the metabolic syndrome (MS) and recurrent pre-eclampsia has not been previously investigated among Egyptian premenopausal women. Pre-eclampsia is a multisystem disorder and its etiopathogenesis has not yet been fully understood. Aim: The aim of the study is to investigate serum PON-1 activity in Egyptian women with MS and assess its potential link with the incidence of recurrent pre-eclampsia. Method: The study group consisted of 60 premenopausal women with MS and 60 healthy controls. In the MS group, 26 patients had past history of recurrent pre-eclampsia. The enzymatic activity of serum PON-1 was measured by spectrophotometer. Serum lipids were measured by enzymatic colorimetric methods using a Hitachi auto-analyzer. Results: MS cases with and without recurrent pre-eclampsia showed significantly reduced PON-1 activity compared to healthy controls. Significant negative correlations were observed between PON-1 levels and BMI, SBP, DBP, serum total cholesterol, TG and LDL-C and positive correlation with HDL–C in MS cases either with or without recurrent pre-eclampsia. In addition, MS cases with history of recurrent pre-eclampsia showed significantly lower levels of PON-1 than those without. Conclusions: Serum PON-1 is significantly reduced in women with MS and might alter their lipid profile. Low PON-1 levels could contribute to the great risk of recurrent pre-eclampsia in MS women.
Keywords: Serum PON-1,metabol¬ic syndrome,recurrent pre-eclampsia,serum lipids,women.